Fast decolorization of azo dyes in alkaline solutions by a thermostable metal‑tolerant bacterial laccase and proposed degradation pathways - Navas, Laura Emilce (2020)
Biocatalytic decolorization of azo dyes is hampered by their recalcitrance and the characteristics of textile effluents. Alkaline pH and heavy metals present in colored wastewaters generally limit the activity of enzymes such as laccases of fungal origin; this has led to an increasing interest in bacterial laccases. In this work, the dye decolorization ability of LAC_2.9, a laccase from the thermophilic bacterial strain Thermus sp. 2.9, was investigated. Its resistance towards different pHs and toxic heavy metals frequently present in wastewaters was also characterized. LAC_2.9 was active and highly stable in the pH range of 5.0 to 9.0. Even at 100 mM Cd+2, As+5 and Ni+2 LAC_2.9 retained 99%, 86% and 75% of its activity, respectively. LAC_2.9 was capable of decolorizing 98% of Xylidine, 54% of RBBR, 40% of Gentian Violet, and 33% of Methyl Orange after 24 h incubation at pH 9, at 60 °C, without the addition of redox mediators. At acidic pH, the presence of the mediator 1-hydroxybenzotriazole generally increased the catalytic effectiveness. We analyzed the degradation products of laccase-treated Xylidine and Methyl Orange by capillary electrophoresis and mass spectrometry, and propose a degradation pathway for these dyes. For its ability to decolorize recalcitrant dyes, at pH 9, and its stability under the tested conditions, LAC_2.9 could be effectively used to decolorize azo dyes in alkaline and heavy metal containing effluents.